2013
DOI: 10.1182/blood-2012-09-456988
|View full text |Cite
|
Sign up to set email alerts
|

Denileukin diftitox (ONTAK) induces a tolerogenic phenotype in dendritic cells and stimulates survival of resting Treg

Abstract: Key Points• ONTAK blocks DC maturation by coreceptor downmodulation and inhibition of Stat3 phosphorylation to induce a tolerogenic phenotype.• ONTAK kills activated CD4T cells but stimulates antiapoptosis in resting T reg by engagement and stimulation through CD25.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 47 publications
1
40
0
Order By: Relevance
“…A recent study even reported induction of tolerance following Ontak therapy. 36 Similar to the observations in the murine studies, results in patients may have been confounded by the co-depletion of tumor-reactive effector T cells.…”
Section: Introductionsupporting
confidence: 62%
“…A recent study even reported induction of tolerance following Ontak therapy. 36 Similar to the observations in the murine studies, results in patients may have been confounded by the co-depletion of tumor-reactive effector T cells.…”
Section: Introductionsupporting
confidence: 62%
“…Whether β-catenin in DCs adversely affects antitumor efficacy of human DC vaccines has not been investigated. Interestingly, in a clinical trial of a DC cancer vaccine against melanoma in combination with regulatory T-cell depletion with unexpected reduced efficacy, DCs were shown to exhibit increased expression of β-catenin and a tolerogenic phenotype (44), suggesting that activation of β-catenin in human DCs might similarly suppress their function and therefore blocking β-catenin could potentially provide therapeutic benefit. Our findings that β-catenin in DCs exerts opposite functions during different phases of …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Treg-depleting drugs appeared to have paradoxical immunologic effects that could impair the activity of DC vaccination (e.g., depletion of NK cells, induction of tolerogenic DCs, and promotion of nonactivated Treg survival; ref. 69).…”
Section: Combinations To Combat Tolerance Induced By Immunosuppressivmentioning
confidence: 99%